Chemical Constituents of Essential Oil from Lippia sidoides Cham. (Verbenaceae) Leaves Cultivated in Hidrolândia, Goiás, Brazil - Sandra Ribeiro de Morais; Thiago Levi Silva Oliveira; Maria Teresa Freitas Bara; Edemilson Cardoso da Conceição; Maria Helena Rezende; Pedro Henrique Ferri; José Realino de Paula (International Journal of Analytical Chemistry)
Several studies involving the family Verbenaceae, occurring in the Brazilian Cerrado, have emphasized the popular use of many aromatic species. We highlight the use of Lippia sidoides Cham., known as “alecrim pimenta,” native to northeastern Brazil and northern Minas Gerais. Leaves of this species were collected in antropized Brazilian Cerrado area, in Hidrolândia, Goiás, and their essential oils were extracted by hydrodistillation in a Clevenger-type apparatus and thereafter analyzed GC/MS. Among the compounds identified in this study were the most abundant oxygenated monoterpenes, followed by sesquiterpenes hydrocarbons. The oxygenated monoterpene 1,8-cineole was the major constituent followed by isoborneol and bornyl acetate. The chemical composition of essential oil described in this paper differs from that described in the literature for L. sidoides found in its native environment, where the major constituents are thymol and carvacrol.